The RNA binding protein La/SS-B promotes RIG-I-mediated type I and type III IFN responses following Sendai viral infection. Issue 1 (December 2017) - Mahony, Rebecca; Broadbent, Lindsay; Maier-Moore, Jacen; Power, Ultan; Jefferies, Caroline
Abstract La/SS-B (or La) is a 48 kDa RNA-binding protein and an autoantigen in autoimmune disorders such as systemic lupus erythematosus (SLE) and Sjögren's syndrome (SS). La involvement in regulating the type I interferon (IFN) response is controversial - acting through both positive and negative regulatory mechanisms; inhibiting the IFN response and enhancing viral growth, or directly inhibiting viral replication. We therefore sought to clarify how La regulates IFN production in response to viral infection. ShRNA knockdown of La in HEK 293 T cells increased Sendai virus infection efficiency, decreased IFN-β, IFN-λ1, and interferon-stimulated chemokine gene expression. In addition, knockdown attenuated CCL-5 and IFN-λ1 secretion. Thus, La has a positive role in enhancing type I and type III IFN production. Mechanistically, we show that La directly binds RIG-I and have mapped this interaction to the CARD domains of RIG-I and the N terminal domain of La. In addition, we showed that this interaction is induced following RIG-I activation and that overexpression of La enhances RIG-I-ligand binding. Together, our results demonstrate a novel role for La in mediating RIG-I-driven responses downstream of viral RNA detection, ultimately leading to enhanced type I and III IFN production and positive regulation of the anti-viral response.